Validez interna y utilidad diagnóstica del Eating Disorders Inventory en mujeres mexicanas Internal validity and diagnostic utility of the Eating Disorder Inventory, in Mexican women - Eduardo García-García; Verónica Vázquez-Velázquez; Juan Carlos López-Alvarenga; Denise Arcila-Martínez (Salud Pública de México, 2003)
OBJETIVO: Determinar la utilidad diagnóstica y la validez interna del Eating Disorder Inventory (EDI-2) en mujeres mexicanas. MATERIAL Y MÉTODOS: De octubre de 2000 a enero de 2001 se invitó a participar a todas las mujeres que a juicio de los psiquiatras de la consulta de anorexia del Instituto Nacional de Ciencias Médicas y Nutrición Salvador Zubirán, de la Ciudad de México, padecían anorexia nervosa o bulimia, sin otra patología psiquiátrica. Es un estudio observacional, comparativo, transversal y prolectivo de dos grupos de mujeres: pacientes de la Clínica de Anorexia del Instituto y de una escuela de la Ciudad de México. Se realizó una entrevista clínica estructurada como estándar de oro (SCID/Manual Diagnóstico y Estadístico de los Trastornos Mentales) y la aplicación del Eating Disorder Inventory. El análisis estadístico incluyó t de Student para muestras independientes, coeficiente alpha de Cronbach, sensibilidad, especificidad, valor predictivo positivo y negativo. RESULTADOS: No hubo diferencias significativas en peso, talla e índice de masa corporal entre los grupos. La edad de las mujeres sin trastorno alimentario fue menor (16.7±2.8 vs. 19.9±4.3, p=0.004). La calificación total del Eating Disorder Inventory fue claramente diferente (53.8±32.4 mujeres sin trastorno alimentario vs. 146.3±45.6 pacientes, p<0.001). Para todas las subescalas los coeficientes alpha de Cronbach fueron superiores a 0.85. Para la calificación total se sugiere un punto de corte sensible de 80 [sensibilidad 90.9 (IC 95% 69.4-98.4, especificidad 80 (IC 95% 58.7-92.4)], y uno específico de 105 [sensibilidad 81.8 (IC 95% 59-94), especificidad 89.3 (IC 95% 70.6-97.2)]. CONCLUSIONES: El Eating Disorder Inventory es útil para investigar trastorno alimentario, con coeficientes de validez interna altos en la población estudiada. OBJECTIVE: To assess the diagnostic utility and internal validity of the Eating Disorder Inventory (EDI-2) in Mexican women. MATERIAL AND METHODS: An observational, cross-sectional study was conducted between October 2000 and January 2001. The sample population consisted of two groups of women: patients diagnosed with anorexia nervosa or bulimia, but no other psychiatric pathology, seen by psychiatrists at the Instituto Nacional de Ciencias Médicas y Nutrición Salvador Zubirán (National Institute of Medical Sciences and Nutrition Salvador Zubirán), and a randomly selected sample of women from a school in Mexico City. A structured interview was conducted using SCID/DSM-IV as the gold standard. Finally the EDI-2 was administered. Statistical analysis was performed using Student's t test for independent samples, Cronbach's alpha test, and calculation of sensitivity, specificity, and positive and negative predictive values. RESULTS: No significant differences were found for weight, height, and body mass index. Women with no eating disorders were younger than those with eating disorders (16.7±2.8 vs. 19.9±4.3, p=0.004). The EDI-2 total score was clearly different between the groups (53.8±32.4 vs. 146.3±45.6 respectively, p<0.001). All Cronbach's alpha coefficients for all subscales were over 0.85. For the total score, a sensitive cutoff point of 80 (sensitivity 90.9, 95% confidence interval [CI] 69.4 to 98.4; specificity 80, 95%CI 58.7 to 92.4) and a specific cutoff point of 105 (sensitivity 81.8, 95%CI 59 to 94; specificity 89.3, 95%CI 70.6 to 97.2) are recommended. CONCLUSIONS: The EDI-2 has a high internal validity and should be a useful tool to assess eating disorders.